Ultrasensitive nonenzymatic real-time hydrogen peroxide monitoring using gold nanoparticle-decorated titanium dioxide nanotube electrodes - Kader, Md. Ashraful; Nina Suhaity, Azmi; Kafi, A. K. M.; Hossain, Md. Sanower; Jose, Rajan; Goh, Khang Wen (MDPI, 2023)
An amperometric enzyme-free hydrogen peroxide (H2O2) sensor was developed by catalytically stabilizing active gold nanoparticles (Au NPs) of 4–5 nm on a porous titanium dioxide nanotube (TiO2 NTs) electrode. The Au NPs were homogeneously distributed on anatase TiO2 NTs with an outer diameter of ~102 nm, an inner diameter of ~60 nm, and a wall of thickness of ~40 nm. The cyclic voltammogram of the composite electrode showed a pair of redox peaks characterizing the electrocatalytic reduction of H2O2. The entrapping of Au NPs on TiO2 NTs prevented aggregation and facilitated good electrical conductivity and electron transfer rate, thus generating a wide linear range, a low detection limit of ~104 nM, and high sensitivity of ~519 µA/mM, as well as excellent selectivity, reproducibility, repeatability, and stability over 60 days. Furthermore, excellent recovery and relative standard deviation (RSD) were achieved in real samples, which were tap water, milk, and Lactobacillus plantarum bacteria, thereby verifying the accuracy and potentiality of the developed nonenzymatic sensor.